The role of prefrontal cortex in a moral judgment task using functional near‐infrared spectroscopy. Issue 11 (25th September 2018) - Dashtestani, Hadis; Zaragoza, Rachel; Kermanian, Riley; Knutson, Kristine M.; Halem, Milton; Casey, Aisling; Shahni Karamzadeh, Nader; Anderson, Afrouz A.; Boccara, Albert Claude; Gandjbakhche, Amir
Abstract: Background: Understanding the neural basis of moral judgment (MJ) and human decision‐making has been the subject of numerous studies because of their impact on daily life activities and social norms. Here, we aimed to investigate the neural process of MJ using functional near‐infrared spectroscopy (fNIRS), a noninvasive, portable, and affordable neuroimaging modality. Methods: We examined prefrontal cortex (PFC) activation in 33 healthy participants engaging in MJ exercises. We hypothesized that participants presented with personal (emotionally salient) and impersonal (less emotional) dilemmas would exhibit different brain activation observable through fNIRS. We also investigated the effects of utilitarian and nonutilitarian responses to MJ scenarios on PFC activation. Utilitarian responses are those that favor the greatest good while nonutilitarian responses favor moral actions. Mixed effect models were applied to model the cerebral hemodynamic changes that occurred during MJ dilemmas. Results and conclusions: Our analysis found significant differences in PFC activation during personal versus impersonal dilemmas. Specifically, the left dorsolateral PFC was highly activated during impersonal MJ when a nonutilitarian decision was made. This is consistent with the majority of relevant fMRI studies, and demonstrates the feasibility of using fNIRS, with its portable and motion tolerant capacities, to investigate the neural basis of MJ dilemmas. Abstract : In this paper, we: (a) Investigate the neural basis of personal and impersonal moral judgment. (b) Investigate prefrontal activity for utilitarian versus nonutilitarian responses. (c) Functional near‐infrared spectroscopy is used as neuroimaging modality. (d) Higher activity over left dorsolateral prefrontal cortex during impersonal dilemmas. (e) This high activation was a result of nonutilitarian decision‐making.